Noncity. Part 2 - Bokov, Andrey (project baikal, 2021)
Andrey Bokov explores the Soviet space and its three stages, its stable characteristics and evolution of relationship between a city and a village. He evaluates the significance of production for Soviet cities and analyzes the evolution of the social structure of the Soviet society. Bokov highlights the changes in the role of Soviet architects and architectural language and the impact of the post-war experience of the West. The author identifies specific characteristics of post-Soviet cities of the RF and the relationship between business, power and society. He underlines the lack of systematic approach in the post-Soviet spatial and social development. He suggests possible ways for further transformation of the structure of the Russian space.
Keywords: Soviet city; village; spatial development; architecture; infrastructure; agglomeration